2021
DOI: 10.1002/pan3.10249
|View full text |Cite
|
Sign up to set email alerts
|

Combining data from consumers and traditional medicine practitioners to provide a more complete picture of Chinese bear bile markets

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
(76 reference statements)
2
13
0
Order By: Relevance
“…All consumers in our sample would pay more in these severe disease scenarios, suggesting that they were originally compromising on preferred attributes to save money when the need for a product is less urgent (Dutton et al., 2011). In addition, our CPS showed that consumers were reluctant to make their own treatment decisions when they were severely ill, supporting previous findings that medical practitioners are important sources of external advice on bear bile treatments in China (Hinsley et al., 2021). This could be related to consumers’ poor knowledge of how bile is used in treatment because when knowledge of a product is low, people employ heuristics based on social influence to make purchasing decisions (Wood & Hayes, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…All consumers in our sample would pay more in these severe disease scenarios, suggesting that they were originally compromising on preferred attributes to save money when the need for a product is less urgent (Dutton et al., 2011). In addition, our CPS showed that consumers were reluctant to make their own treatment decisions when they were severely ill, supporting previous findings that medical practitioners are important sources of external advice on bear bile treatments in China (Hinsley et al., 2021). This could be related to consumers’ poor knowledge of how bile is used in treatment because when knowledge of a product is low, people employ heuristics based on social influence to make purchasing decisions (Wood & Hayes, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Although online surveys may produce a less representative sample of the public than face‐to‐face surveys, they are particularly useful for accessing difficult‐to‐reach groups. This was important because previous work on Chinese bear bile markets shows that face‐to‐face surveys find relatively few actual consumers (e.g., Dutton et al., 2011; Hinsley et al., 2021). We also chose to use an anonymous online survey because they improve honesty in reporting of sensitive and illegal behavior compared with face‐to‐face surveys (Kreuter et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations